Cytogenetic effect of Alternanthera philoxeroides (alligator weed) on Agasicles hygrophila (Coleoptera: Chrysomelidae) in its native range - Telesnicki, Marta Cecilia (2011)
Plant genotypic effects can alter insects' ability of utilizing their host plant. Alligator weed, Alternanthera philoxeroides, is a South American amphibious Amaranthaceae, which invades aquatic and terrestrial habitats. Populations with varying morphotypes and cytotypes were identified and further associated with a polyploid hybrids complex in Argentina, which probably is the centre of origin and diversification of alligator weed. The current model of the hybrid complex formation proposes that diploid ancestors gave rise to allotetraploids and allohexaploids.Agasicles hygrophila is a monophagous chrysomelid beetle which successfully controls A. philoxeroides in regions with mild winters and where the weed grows in aquatic habitats. However, plant genetic characteristics could constrain insect development and reproduction, providing an alternative explanation for the restricted success of biological control of alligator weed with A. hygrophila. We investigated the effect of four A. philoxeroides populations with varying cytogenetical characteristics on plant-insect interaction with A. hygrophila in the native range of the weed. The insect's life cycle on each host population was studied. In addition, the genetic relationships among the weed populations was explored using dot blot analysis.Plant population affected insect survival and fecundity, but not life cycle length nor third larval instar mortality, pupal mortality or female proportion. Plant internode diameter was not a restriction for insect pupation. All hexaploid populations of A. philoxeroides, as well as the close related A. aquatica, hybridized with the tetraploid population probe with similar intensity, meaning that this population is a component of their polyploid genome.